Valproate serum concentrations in patients with hypoalbuminemia and medical complications - VandenBerg, Amy (Ment Health Clin, 2018)
INTRODUCTION: Valproic acid (VPA) and its derivatives are highly protein bound with free fraction increasing with dose and serum concentration. Consensus guidelines regarding dose adjustment for hypoalbuminemia are not available. METHODS: A literature search was performed using PubMed to identify articles with the following key terms: “valproate,” “valproic acid,” “protein binding,” “albumin,” and “hypoalbuminemia.” We report our findings as well as 5 cases involving pharmacokinetic impact of hypoalbuminemia on valproate. RESULTS: A previously published model for normalizing VPA serum concentration for hypoalbuminemia in patients with epilepsy was compared to results for 5 cases (4 female, 1 male) in which VPA was used for psychiatric illness. Only 1 of the cases had free serum concentrations in the range that would be expected with the model. Free concentrations ranged from 22% to 83% with no clear relationship to other factors (weight, age, serum creatinine, or dose). Female patients with similar albumin had higher free fractions than the 1 male patient. DISCUSSION: Due to the variability in pharmacokinetic impact of hypoalbuminemia, it is important to monitor patients closely for signs of VPA toxicity in cases involving altered albumin levels. It would be prudent to use free serum VPA concentrations when patients experience fluctuations in albumin or have unexpected response to medication.